Economic origins of dictatorship and democracy - Acemoglu, Daron; Robinson, James A., 1960- (Cambridge University Press, 2006)
This book is the first to use modern social science methodology systematically to explain why some countries are democracies while others are not. Why does democracy sometimes persist and consolidate while other times it collapses? The treatment shows that whether or not a society becomes democratic depends on several factors.